Ultra-wideband impulse radio based temperature sensor network - Li, Erfeng (2014)
With the overwhelming development of Ultra-Wide Band impulse radio (UWB-IR) technology,it has derived a large variety of application for wireless sensor network. It can be applied on monitoring, automation control, medical testing and other purposes. This UWB-IR technology features a couples of advantages, i.e., its multipath resistance characteristics, low power consumption and low cost architecture compared with other existing narrow band carrier wave based networks. This project aims to build a building energy management system, which uses the integration of temperature sensor to gather information and give feedback to MSP430 module for automated control. The configuration and specification of I2C module of TEMP sensor and the MSP430 module will be given. Design for the communication between the TEMP sensor and MSP430 module through programming language C++ will be displayed in details. Transmission of data through UWB-IR will also be discussed and conducted.